(untitled) (Clinics, 2023)
Objectives: To analyze the perinatal outcomes of Perinatally acquired HIV Infection (PHIV) in pregnant women. Method: This retrospective cohort study included singleton pregnancies in Women Living with HIV (WLH) between 2006 and 2019. Patient charts were revised, and maternal characteristics, type of HIV infection (perinatal vs. behavioral), Antiretroviral Therapy (ART) exposure, and obstetric and neonatal outcomes were assessed. The HIV-related aspects considered were: Viral Load (VL), CD4+ cell count, opportunistic infections, and genotype testing. Laboratory analyses were performed at baseline (first appointment) and 34 weeks of gestation. Results: There were 186 WLH pregnancies, and 54 (29%) patients had PHIV. Patients with PHIV were younger (p < 0.001), had less frequently stable partnerships (p < 0.001), had more commonly serodiscordant partners (p < 0.001), had a longer time on ART (p < 0.001), and had lower rates of undetectable VL at baseline (p = 0.046) and at 34 weeks of gestation (p < 0.001). No association was observed between PHIV and adverse perinatal outcomes. Among patients with PHIV, third trimester anemia was associated with preterm birth (p = 0.039). Genotype testing was available only for 11 patients with PHIV, who presented multiple mutations related to ART resistance. Conclusions: PHIV did not seem to increase the risk of adverse perinatal outcomes. However, PHIV pregnancies have a higher risk of viral suppression failure and exposure to complex ARTs.